2018
DOI: 10.24093/awej/vol9no3.4
|View full text |Cite
|
Sign up to set email alerts
|

English Language Learning Motivation and English Language Learning Anxiety in Saudi Military Cadets: A Structural Equation Modelling Approach

Abstract: This study aims to investigate English language learning motivation and English language learning anxiety in Saudi military cadets. Some 174 Saudi military cadets completed a questionnaire specifically developed to be used in the context of Saudi Arabia. Structural Equation Modelling (SEM) was used to analyse a proposed model using Analysis of Moment Structures (AMOS) version 21. The study found that the students' language learning effort was determined by their Ideal L2 Self and their positive attitudes towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Finally, each motivation factor is strongly correlated with other motivational factors (Table 5) except instrumentality prevention with intended effort, ideal L2 self, attitudes towards language learning, attitudes towards L2 community, and cultural interest. These findings are aligned with previous studies [6,16,[57][58][59][60][61]. On the other hand, we found that anxiety factor exhibits negative relationship with intend effort, ideal L2 self, family influence, attitudes towards language learning, attitudes towards L2 community, and cultural interest.…”
Section: Efa To Generate L2 Motivationsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, each motivation factor is strongly correlated with other motivational factors (Table 5) except instrumentality prevention with intended effort, ideal L2 self, attitudes towards language learning, attitudes towards L2 community, and cultural interest. These findings are aligned with previous studies [6,16,[57][58][59][60][61]. On the other hand, we found that anxiety factor exhibits negative relationship with intend effort, ideal L2 self, family influence, attitudes towards language learning, attitudes towards L2 community, and cultural interest.…”
Section: Efa To Generate L2 Motivationsupporting
confidence: 92%
“…These findings are aligned with previous studies [62,63]. The results also indicate that anxiety has a positive correlation with ought to L2 self and instrumentality motivation [58,59,64]. Table 5 shows correlation matrix of CFA.…”
Section: Efa To Generate L2 Motivationsupporting
confidence: 89%
“…Of the three constructs of the L2MSS, the IL2S is the most salient because it has been found in almost all the previous studies that it is the most significant variable in predicting the learning effort of L2 students (Alqahtani, 2018b;Csizér & Kormos, 2009;Kormos, Kiddle, & Csizér, 2011;Taguchi, Magid, & Papi, 2009). In some studies, the IL2S accounted for more than 40% of the variance in the learning effort of L2 students, such as 45% in Alqahtani's (2018a) study. In the field of L2 motivation studies, these figures can be regarded as exceptionally high (Dörnyei & Ushioda, 2011).…”
Section: The L2mssmentioning
confidence: 84%
“…The results of a number of studies reveal an even stronger impact (Alqahtani, 2017b;Csizér & Kormos, 2009;Islam, Lamb, & Chambers, 2013). The L2LE has been referred to using a number of terms interchangeably; for example, "Language Learning Attitudes" (LLA) (Alqahtani, 2018a;2018b), "Attitudes to L2 Learning" (You, Dörnyei, & Csizér, 2016), "Attitudes to Learning English" (Islam et al, 2013), and "L2 Learning Attitude" (Csizér & Kormos, 2008b). In this study, the third construct of the L2MSS is referred to as LLA.…”
Section: The L2mssmentioning
confidence: 99%
“…In other parts of the world, such as South America, positive attitudes toward learning English prevail due to the language's importance in the job market [19][20]. Similar trends were observed in Kuwait, Taiwan, and Malaysia [23][24][25]. Indonesian students have also shown favorable attitudes toward learning English [26][27][28].…”
Section: Introductionmentioning
confidence: 88%